On pseudo-complex bases for monogenic polynomials - Cruz, Carla (2012)
In the recent past, the problem of constructing bases for spaces of monogenic polynomials, in the framework of Clifford Analysis, has been considered by several authors, using different methods. In this talk we consider bases of 3D monogenic polynomials isomorphic to the complex powers, which are particularly easy to handle, from the computational point of view. Explicit constructions of such polynomial bases are performed and a numerical cost comparison with the well known Fueter polynomial basis is carried out.